Physiological and Metabolic Changes of Purslane (Portulaca oleracea L.) in Response to Drought, Heat, and Combined Stresses - Jin, Rui; Wang, Yanping; Liu, Ruijie; Gou, Junbo; Chan, Zhulong (Frontiers in Plant Science, 2016)
Purslane (Portulaca oleracea L.) is a fleshy herbaceous plant. So far, little information is available on the response of this plant to combined drought and heat stress. In this study, changes in physiological and metabolic levels were characterized after treatments with drought, heat and combined stresses. Both individual and combined stress treatments increased malondialdehyde (MDA), electrolyte leakage (EL), O2•− and activities of superoxide dismutase (SOD), peroxidase (POD), while declined chlorophyll content. No significant differences were found between control and treatments in leaf water content (LWC) and catalase (CAT) activity. Additionally, 37 metabolic compounds were detected in purslane. Through pathway analysis, 17 metabolites were directly involved in the glycolysis metabolic pathway. The present study indicated that combined drought and heat stress caused more serious damage in purslane than individual stress. To survive, purslane has a high capability to cope with environmental stress conditions through activation of physiological and metabolic pathways.